Physical activity: Physical activity dose‐response effects on mental health status in older adults - Kerry Mummery; Grant Schofield; Cristina Caperchione (Elsevier, 2004)
Abstract Objective: The purpose of this study was to examine the dose‐response relationship between physical activity and mental health, comparing two recommended levels of physical activity involvement. The two current physical activity recommendations used to study the dose‐response relationships in a sample of older adults were 150 minutes per week and 420 minutes per week. Method: Data were collected on a sample (n=337) of independent living older adults ranging from 55 to 89 years of age (mean age 65.2 years) using a computer‐assisted telephone interview (CATI) survey. Activity status was assessed using the Active Australia questionnaire, whereas health status was assessed using the SF‐12 health survey questionnaire. Results: Participants classed as moderately active (150-420 minutes per week) and highly active (>420 minutes per week) displayed significantly higher mental health status than those who were classified as inactive (>150 minutes per week) when controlling for physical health status. Further analysis failed to reveal any significant difference in mental health status between moderately and highly active participants. Conclusion: When controlling for the variability in mental health status relating to physical health, individuals meeting current guidelines of 150 minutes of physical activity per week displayed higher mental health than those who did not. Increased levels of activity showed no reliable increase in health status. Implications: The benefits of moderate levels of physical activity were supported for older adults. In terms of mental health, recent recommendations for increased amounts of daily activity were not supported.